Effects of IIUM food waste compost and inorganic fertilizer on growth performance of Brassica juncea (mustard) - Abu Samah, Mohd Armi; Abdul Halim, Muhammad Ikram; Ibrahim, Mohd Zulfadzli; Ahmad, Mohammad Norazmi; Mohd Jan, Nurul Hafiza; Kamarudin, Mohd Khairul Amri (Science and Engineering Research Support Society, 2020)
Food waste is one of the most contributors to the number of solid waste generation as eating is a daily activity for human life. Furthermore, food waste composting can contribute to the economic growth of a country as well as mitigating other environmental issues such as water pollution and emission of greenhouse gases and also provide the surrounding area of the place is clean and tidy. This study aims to determine the effects of IIUM food waste compost and inorganic fertilizer on the growth performance of Brassica juncea (mustard). The application of fertilizers were divided into four treatments, T1 (control without any fertilizer), T2 (100% food waste compost), T3 (100% inorganic fertilizer), and T4 (50% food waste compost + 50% inorganic fertilizer). The study was carried out at the Glasshouse Nursery Complex, International Islamic University Malaysia. The study was consist of several stages starting from the sowing of the seeds, transplanting into polybags, planting, harvesting, and collecting data followed by laboratory analysis and finalized with analyzing data statistically. A total number of 36 experimental units involving four levels of treatments were conducted in the greenhouse. There were three blocks, and each block has three replications for each treatment. The total number of experimental units for each block were 12 units. The experimental design was a factorial experiment in the form of Randomized Complete Block Design (RCBD). The research was conducted to determine the effect of different treatments of fertilizers which from IIUM food waste compost and inorganic fertilizer on the morphological characteristics (plant height and the number of leaves), the biomass of plant (Fresh weight (FW) and Dry weight ( DW)), soil pH and nitrogen (N) uptake by Brassica juncea. As a result, There were no significant differences during the first and second weeks of planting for each of the treatments. The treatments showed significant results (p≤0.05) on the plant height as T4 produced the tallest plant, which was 11.77cm followed by other treatments (T3 = 10.48cm, T2 = 7.32cm, T1 = 6.89cm) other treatments in the fourth weeks. The number of leaves produced and biomass recorded by T4 (10, FW = 23.2664g, DW = 1.3036g) and T3 (10, FW = 22.0613g, DW = 1.0839g) also among the highest compared to T2 (7, FW = 5.1434g, DW = 0.2116g) and T1 (4, FW = 71.5893g, DW = 0.1294g). However, soil pH at harvest recorded by T2 was the highest (5.27) compared with other treatments where the result was obtained by other treatments (T1 = 5.07, T4 = 5.02, T3 = 4.58). Additionally, the total N content in soil at harvest for T3 and T4 as both showed a lower amount of N (0.06%) as compared to other treatments (T1 = 0.07%, T2 = 0.09%) probably due to the higher N uptake by the plant. Based on the findings of this study, it can be inferred that the combination of food waste compost and inorganic fertilizer (T4) was the best treatment for promoting the growth of Brassica juncea.